# Transformation of f(x,y) = 1 to f(z) where Z=XY

## Main Question or Discussion Point

This is from a chapter on distributions of two random variables. Let X and Y have the pdf f(x,y) = 1, 0<x<1 and 0<y<1, zero elsewhere. Find the cdf and pdf of the product Z=XY.

My current approach has been to plug in X=Z/Y in the cdf P(X<=x) , thus P(Z/Y<=x), and integrate over all values of Y. The integral I've tried to solve is ∫(0 to 1)∫(0 to Z/Y) 1 dxdy (sorry for the formatting).

This is somehow wrong, because from that integral I get z*(ln(1) - ln(0)), which is undefined (unless I'm solving the integral incorrectly, which would actually be a relief).

The correct answer is -ln(z), 0<z<1, though it's amiguous as to whether that's the cdf or pdf.

Thanks for any solutions or suggestions about where my approach is going wrong.

Related Set Theory, Logic, Probability, Statistics News on Phys.org
mathman
-ln(z) is a density function.

When doing the integral note that the upper limit on x is min(1,z/y).

Another way of seeing the same thing... [It looks a little less direct, but there's value in thinking about sums of exponential random variables.]

Let $\tilde X = -ln(X)$, $\tilde Y = -ln(Y)$, and $\tilde Z = -ln(Z) = \tilde X+\tilde Y$, all taking values on $(0,\infty)$. Define the CDF $G(\tilde x)= P(\tilde X\leq \tilde x)= P(X\geq e^{-\tilde x})=1-e^{-\tilde x}$, which is of course also the CDF of $\tilde Y$. Differentiating, we get the PDF $g(\tilde x)=e^{-\tilde x}$. Now we can compute $$P(\tilde Z> \tilde z\geq \tilde X) = \int_0^{\tilde z} P(\tilde x+\tilde Y> \tilde z) g(\tilde x) \text{d}\tilde x = \int_0^{\tilde z} [1- G( \tilde z-\tilde x)] g(\tilde x) \text{d}\tilde x = \int_0^{\tilde z} e^{\tilde x-\tilde z} e^{-\tilde x} \text{d}\tilde x = \int_0^{\tilde z} e^{-\tilde z} \text{d}\tilde x = \tilde z e^{-\tilde z}.$$ This yields $$P(Z<z\leq X) = P(\tilde Z> -ln(z)\geq \tilde X) = [-ln(z)]z.$$ Finally, we notice that (as $Z\leq X$) $$P(Z<z)=P(X<z)+P(Z<z\leq X) = z - [-ln(z)]z = [1-ln(z)]z.$$ If your end goal is a density, you can differentiate for a PDF of $-ln(z)$.

Thanks for the responses. Before I dive into economicsnerd's solution (wow), I'm a bit confused by min(1,Z/Y). When Z<Y, min(1,Z/Y) is Z/Y. When Z>Y, it's 1. So...

∫(0 to 1)∫(0 to Z/Y)dxdy where 0<z<y<1
∫(0 to z)∫(0 to 1)dxdy where 0<y<z<1

Isn't the first integral still undefined? Or am I applying this incorrectly?

The CDF of $Z$ is $$F(z)= P(Z\leq z) = 1- P(Z>z) = 1-P(X\geq Z > z) = 1-\int_z^1 \int_{\frac{z}{x}}^1 1\enspace \text{d}y \enspace \text{d}x = 1-\int_z^1 \left(1-\frac{z}{x}\right) \enspace \text{d}x.$$ What do you get when you compute that integral?